2015
DOI: 10.1186/s12983-015-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Linking habitat suitability to demography in a pond-breeding amphibian

Abstract: IntroductionElucidating the relationship between habitat characteristics and population parameters is critical for effective conservation. Habitat suitability index (HSI) models are often used in wildlife management and conservation practice assuming that they predict species occurrence, abundance and demography. However, the relationship between vital rates such as survival and reproduction and habitat suitability has rarely been evaluated. In this study, we used pond occupancy and mark-recapture data to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 54 publications
5
50
0
Order By: Relevance
“…; Unglaub et al . ), high population densities are assumed to reflect higher quality patches, and the causal relationships are similar to the diffusion‐density relationship we observe: higher resource density leads to slower movement, which leads to higher densities of foraging organisms. In other cases, high population density reflects lower per‐capita habitat quality and higher movement rates; this pattern has been documented by manipulating habitat quality and density in experimental populations (Kuefler, Avgar & Fryxell ).…”
Section: Discussionsupporting
confidence: 61%
“…; Unglaub et al . ), high population densities are assumed to reflect higher quality patches, and the causal relationships are similar to the diffusion‐density relationship we observe: higher resource density leads to slower movement, which leads to higher densities of foraging organisms. In other cases, high population density reflects lower per‐capita habitat quality and higher movement rates; this pattern has been documented by manipulating habitat quality and density in experimental populations (Kuefler, Avgar & Fryxell ).…”
Section: Discussionsupporting
confidence: 61%
“…This evaluation is crucial, because HSMs can only be used for management recommendations if they can be applied on a larger scale (Graf, Mathys, & Bollmann, ; Rechsteiner et al, ). While Rittenhouse et al () and Unglaub et al () evaluated occupancy‐based HSMs based on predictability of independently collected demographic rates, our study uses the opposite approach: We show how independently collected occupancy data can evaluate demographic rates based on a predicted HSM.…”
Section: Discussionmentioning
confidence: 97%
“…Results are still inconsistent across studies (Bean et al 2014, Unglaub et al 2015, but there is an increasing number of examples in birds, where environmental suitability derived from SDMs correlates with other population parameters such as breeding density, territory size, or survival (Table 1). More research is needed on whether the observed correlations can be generalized and identified as causative across birds and whether dynamic distribution models (i.e.…”
Section: Other Applicationsmentioning
confidence: 99%